Ballistic method based on isothermal model for finite shotstart pressure - Seth, Gaya Prasad (Defence Science Journal, 2014)
This communication presents a generalisation of the 'R.D. 38 Method', given by Crow, to the case of finite shotstart pressure. Further here the problem of composite charge for isothermal model has been discussed and the expressions for the maximum pressure and muzzle velocity have been derived.